The Capacity to be Content: Aspirations and Young Adult Catholics in Singapore - Cornelio, Jayeel (Archīum Ateneo, 2015)
Drawing from interviews with young adult Catholics in Singapore, this article discusses aspirations in terms of the capacity to be content. For my informants, the capacity to be content has three aspects: the pursuit of happiness, the questioning of Singapore’s incessant drive for economic growth, and the neglect of those left-behind. Taken collectively, these nuances show that the aspirations of young adult Catholics are effectively a moral critique of the social and economic state of affairs in the city-state. The capacity to be content also informs these young adults’ decision to be involved in welfare activities or even be employed in social work altogether. However, such moral critique’s potential to contest the political status quo is tempered by the resounding opinion that religion and politics do not mix in Singapore. It is precisely by interrogating this tension between their aspirations and their views of the moral state of Singapore that this article is a contribution to this special issue on Christianity and the nation in Southeast Asia.